Piezoelectric Resonance in KH2PO4 Type Crystals Revisited - Levitskii, R. R.; Vdovych, A. S.; Moina, A. P.; Zachek, I. R. (Physics and Chemistry of Solid State, 2015)
Within the framework of proton model with taking into account the piezoelectric interaction with the shear strain , a dynamic dielectric response of KH2PO4 family ferroelectrics and antiferroelectrics is considered. Piezoelectric resonance frequencies of rectangular thin plates of the crystals cut in the (001) plane (0 Z-cut) are calculated, which are found to be in a good agreement with experiment.